PENGARUH PENGGUNAAN PONSEL TERHADAP PERUBAHAN SIKAP PADA REMAJA - Sinapoy, Almyra Soumi; Putri, K. Y. S. (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2021)
This research is motivated by information and communication technology that has increasingly advanced and developed rapidly in the era of digitalization. One part of information technology is communication technology. The most widely used communication technology is nothing but a cell phone. As advances in increasingly sophisticated technology, information technology has become one of the needs and even demands for rapid exchange of information. Sophisticated technology in this era certainly provides a lot of convenience and flexibility as in doing the things we used to do in everyday life in the real world, now we can do it on our cellphones with features that are no less sophisticated and very easy to we use it. However, although there are many positive aspects that we can take from the advancement of technology in the current era, of course there are also many negative sides or deficiencies of sophisticated technological advancements. One example is with the advance of highly sophisticated communication technology, this makes face-to-face communication decline because everything can be accessed through our respective cellphones. Most mobile phone users are none other than teenagers. According to Indonesiana, cell phones have become a multi-functional tool and are also used as one of their daily needs, in addition to being a communication medium, cellphones are also used as a tool to capture moments, be entertainment (play games), be a social media facility, be a source of information, and others.